The benefit of saffron on reducing anxiety symptoms among nursing students - Sumiyarini, Retno; Utami, Khristina Dias; Riyadi, Sujono (MEDIA ILMU KESEHATAN, 2024)
Background: Nursing students have higher levels of anxiety than students of others majors. Common stressors perceived are rigorous courses, a mandatory curriculum requires students facing frequent transitions from classroom to intensive lab and hospital also frequent enforcement of exams. Dealing with those situations, students attempt to deal and cope through the negative mode of action such as consuming alcohol, marijuana, smoking, and drug abuse. It is essential to manage those problems through effective interventionObjective: This study aims to understand the potential effects of saffron to treat anxiety among college students.Methods: We conducted an un-blinded experimental study. 78 nursing students perceiving anxiety, divided into two groups, the saffron group (n 42) and control groups (n 36). Treatment protocol was saffron group received saffron as brewed drinks, while control group drinks regular tea. The treatment duration is two weeks. Outcome assessed with DASS 21 Checklist, at baseline, and after 2 weeks therapy.Results:. Saffron had a more significant impact on the anxiety level among the intervention group. The mean anxiety scores decreased from 13,8 to 9,2 for the saffron group (p 0,0001).Conclusion: Our findings suggest that saffron is effective to reduce anxiety level among nursing students